Neither private contractors nor productive partners: The English fiscal-naval state and London hospitals, 1660–1715. (May 2016) - Neufeld, Matthew
Relations between the Royal Navy and London's great hospitals during the late seventeenth and early eighteenth centuries concerning the care of sick and injured sailors were complicated, fraught and at times riven with conflict. This article surveys the relationship during the late Stuart era between the fiscal-naval state and the hospitals – semi-private institutions with a public mission – and attempts to re-evaluate the usefulness of the concept of partnership for understanding public and private interactions during wartime. The article contends that the state and the hospitals did not form a productive partnership because London's hospitals were obliged to work for the navy in ways that compromised the hospitals' ability to serve their core public.